Diplomasi Public Korea Selatan di Indonesia dalam Mempromosikan Budayanya melalui Korean Culture Center Indonesia - Lestari, Oriza Dian; Lubis, Flori Mardiani; Gustianti, Nurbani Adine (Jurnal Ilmiah Wahana Pendidikan, 2024)
A Country basically cannot act alone in fulfilling its soft power goals abroad, for that the government forms state institutions that can be more flexible in approaching targets of other country's public. It is through this institution that public diplomacy with several dimensions and elements can be implemented as needed by the country of origin. Currently, diplomacy activities are not only carried out by the government, anyone can carry out diplomacy or what is better known as public diplomacy. Public diplomacy is one of the instruments used to increase cooperation in achieving the interests of the state by promoting something we have to foreign publics. One of the countries that has carried out public diplomacy is South Korea which has succeeded in capturing the hearts of the Indonesian people with its unique cultural popularity through the Korean Cultural Center (KCC). This study aims to determine the public diplomacy carried out by South Korea towards Indonesia in promoting its culture through the Korean Cultural Center. The results of the study show that the Korean Cultural Center can be a medium of public diplomacy that is able to help achieve the national interest of South Korea, namely promoting Korean culture to the Indonesian people.